Deciphering the Contribution of γδ T Cells to Outcomes in Transplantation. Issue 12 (December 2018) - McCallion, Oliver; Hester, Joanna; Issa, Fadi
Abstract : Abstract: γδ T cells are a subpopulation of lymphocytes expressing heterodimeric T-cell receptors composed of γ and δ chains. They are morphologically and functionally heterogeneous, innate yet also adaptive in behavior, and exhibit diverse activities spanning immunosurveillance, immunomodulation, and direct cytotoxicity. The specific responses of γδ T cells to allografts are yet to be fully elucidated with evidence of both detrimental and tolerogenic roles in different settings. Here we present an overview of γδ T-cell literature, consider ways in which their functional heterogeneity contributes to the outcomes after transplantation, and reflect on methods to harness their beneficial properties. Abstract : A comprehensive overview of the γδ T cell literature, focusing on the ways in which their functional heterogeneity contributes to outcomes after transplantation, and reflection upon methods to harness their beneficial properties.